2012
DOI: 10.1055/s-0031-1291720
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience of endoscopic submucosal tunnel dissection for upper gastrointestinal submucosal tumors

Abstract: In this pilot study, endoscopic submucosal tunnel dissection (ESTD) of esophageal and cardia SMTs was effective and appeared to be safe. Larger studies that also examine its application for gastric SMTs are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 8 publications
2
81
1
2
Order By: Relevance
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
“…Alternative methods include endoscopic submucosal dissection (ESD), endoscopic submucosal excavation (ESE) and endoscopic full-thickness resection, but these may be associated with unsatisfactory outcomes due to incomplete resection and/or the risk of perforation during the procedure (3)(4)(5). Submucosal tunneling endoscopic resection (STER) has emerged as a novel technique for treating upper gastrointestinal SMTs and has yielded promising results (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). STER possesses multiple advantages over other endoscopic methods, including the maintenance of mucosal integrity, the facilitation of an increased rate of healing and a decreased risk of pleural/abdominal infection.…”
Section: Introductionmentioning
confidence: 99%
“…The submucosal tunnel endoscopic resection technique (STER) is an offshoot of POEM, and allows removal of lesions in the muscularis propria and submucosa [37] .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Gong et al [19] also reported a pilot study of 12 patients (with SMTs located in the esophagus and cardia), which was conducted using endoscopic submucosal tunnel dissection (ESTD), the procedure was more or less similar to STER. The mean size of resected SMTs was around 20 mm, and the mean operation time was around 50 min.…”
Section: Current Techniques Of Full-thickness Resectionmentioning
confidence: 99%